Vitex agnus-castus L. د ا رسة الفعالية البايولوجية لبعض مستخلصات أو ا رق نبات كف مريم - عبود شريفعلي; عبد الله الموسويعبدالامير; حسين عليلؤي (University of Thi-Qar Journal of Science, 2019)
In this study, the antibacterial activity of some Leaves Extracts of (Vitex agnus-castus L.)were determinated against two species of bacteria Escherichia coli and Staphylococcus aurous, These extracts including hot ethanolic 70% extract , hot methanolic 70% extract flavonoid extract , oil extract and essential oils extracts , and the anticancer activity of flavonoid extract was evaluated against two cancer cell lines (HEP-2, AMN3 ). The results showed that flavonoid extract exhibited best antibacterial activity followed by hot ethanolic 70% extract and hot methanolic 70% extract , while oil extract and essential oils extracts showed no antibacterial activity . Anti cancer activity of flavonoid extract showed no anticancer activity against Hep-2and AMN3 cell lines for three concentrations (3.125,6.25,12,5,25 mg/l) in comparison with negative control. Moreover, a photochemical screening of the methanolic extract was revealed that presence of flavonoids,tannins,saponins,phenols,and carbohydrates and absence of proteins and alkaloids